A Brief History of Phantasmagorias - Castigliano, Federico (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The article underlines the connection between the flâneur, as described in Benjamin's studies, and the emblematic places of the modern consumer society, centered on the symbolic value of the merchandise. First of all, the philosophical meaning of the word "phantasmagoria" will be clarified, analyzing its origin and use, in particular with reference to the Marxist critical tradition that goes from Adorno to the more recent works of Andreotti and Lahiji. The origins of the flâneur in nineteenth-century Paris will be then investigated, emphasizing the relationship between the character of the walker in the metropolis and the literary tradition, the new aesthetics, and the lifestyle that defines modernity. In the central part of the essay, the stages that have marked the history of phantasmagoria will be examined, considering the technological evolution and the type of experiences offered to the consumer: the Parisian passages, the modern metropolis, the department stores, the world’s fair, the shopping malls, the theme parks, the "superplaces" and, finally, the spaces of the virtual architecture. In particular, the latest trends in experiential and omnichannel shopping will be highlighted, to demonstrate the impact of media technology on the use of real and virtual consumer spaces. The hypotheses I am trying to demonstrate are therefore the following: 1. The historical continuity between 19th-century European modernity and the contemporary world. 2. The centrality of the flâneur in the urban scene, considered as an observer and user of the spectacle of the metropolis and the aesthetic experience it offers. 3. The importance of shopping as a ritual, an activity that seems to meet a fundamental need of today's man.